'Thinking that somebody's going to delay [a tonsillectomy] for one to two years is quite horrifying really': a qualitative feasibility study for the NAtional Trial of Tonsillectomy IN Adults (NATTINA Part 2). (10th November 2016) - McSweeney, L.A.; O'Hara, J.T.; Rousseau, N.S.; Stocken, D.D.; Sullivan, F.; Vale, L.; Wilkes, S.; Wilson, J.A.; Haighton, C.A.
Abstract : Objectives: Level one evidence on the value of adult tonsillectomy versus non‐surgical management remains scarce. Before embarking on a costly national randomised controlled trial, it is essential to establish its feasibility. Design: Feasibility study with in‐depth qualitative and cognitive interviews. Setting: ENT staff and patients were recruited from nine hospital centres across England and Scotland. Participants: Patients who were referred for tonsillectomy ( n = 15), a convenience sample of general practitioners ( n = 11) and ear, nose and throat staff ( n = 22). Main outcome measures: To ascertain whether ear, nose and throat staff would be willing to randomise patients to the treatment arms. To assess general practitioners' willingness to refer patients to the NAtional Trial of Tonsillectomy IN Adults (NATTINA) centres. To assess patients' willingness to be randomised and the acceptability of the deferred surgery treatment arm. To ascertain whether the study could progress to the pilot trial stage. Results: Ear, nose and throat staff and general practitioners were willing to randomise patients to the proposed NATTINA. Not all ENT staff were in equipoise concerning the treatment pathways. Patients were reluctant to be randomised into the deferred surgery group if they had already waited a substantial time before being referred. Conclusions: Findings suggest that the NATTINA may not be feasible. Proposed methods could not be realistically assessed without a pilot trial. Due to the importance of the question, as evidenced by NATTINA clinicians, and strong support from ENT staff, the pilot trial proceeded, with modifications.